Study on the effects of laser shock peening on the microstructure and properties of 17-7PH stainless steel - Li, Kangwen; Yu, Weichen; Li, Yaping; Bao, Haidong; Cao, Yupeng; Wang, Yujiang (Frontiers in Materials, 2024)
To investigate the surface integrity of 17-7PH stainless steel welded structural components used in aviation, laser shock peening (LSP) with different power densities was applied to stainless steel welded joints. The microstructural morphology, structural features, full-width at half-maximum, microhardness, and surface roughness of the stainless steel welded joint specimens before and after LSP were characterized and measured using SEM, TEM, XRD, a microhardness tester, and a highresolution confocal microscope. The effects of different laser power densities on the microstructure and properties of the stainless steel welded joints were explored. Results indicate that the stainless steel welded joints exhibit a typical BCC phase. Laser shock peening promotes grain refinement in the welded joints, leading to the phase transformation of residual austenite into martensite. The surface roughness of the specimen is positively correlated with laser power density. At a power density of 5.17 GW/cm², the surface roughness increased to 1.919 μm, which is 117.08% higher than that of the non-peened specimen. The microhardness of the specimens shows a decreasing trend with increasing power density. When the power density is 2.79 GW/cm² , the microhardness of the specimen significantly increases to 462.94 HV0.5, which is 22.26% higher than that of the nonpeened specimen.